Penjadwalan Kompetisi Sepak Bola Liga PSN Ngada Menggunakan Algoritma Honey Bee Mating Optimization - Firdhansyah Abubekar; Yufis Azhar; Agus Eko Minarno (Universitas Muhammadiyah Malang, 2020)
Soccer scheduling is one of the key factors so that the competition can be done well or not. Poor scheduling will affect the condition of the team that will compete, because a poor schedule will prevent the team from preparing their team well for the next match. For this research, we will discuss a system that can determine scheduling and also discuss issues that must be resolved in the big phase 10 PSN Ngada competition that uses a competition system. In this study, we will use the marriage honey bee optimization algorithm, this algorithm was chosen because it is easy to use and can produce quite good scheduling. This algorithm allows the formation of scheduling that avoids predetermined boundaries of combinations that have been formed, which have passed the process of mating flights, crossover, mutations and queen selection. This cycle will continue to run until it reaches the specified and choose scheduling with the best fitness value.